Strategies for Promoting Rights and Equality of the Disabled and Caretakers in Tak Province - Thepnigorn, Saksayam; Wongkhumchan, Saran; Kannin, Soranee (Ratchaphruek Journal, 2023)
The objectives of this research were to 1) examine the condition, problems, and factors related to the promotion of rights and equality of the disabled and caretakers, and 2) evaluate strategies in promoting the rights and equality of the disabled and caretakers in Tak province. The data collection was from 379 participants, using non-proportional stratified random sampling, including heads of involved governmental organizations, executives and staff of local administration organizations, directors of the Division of Social Welfare, chairpersons of the clubs of disability, caretakers of service centers and village headmen, together with 35 informers were university professors, government officials, and sub-district staff. The research tools were questionnaires, and interview forms. The statistics used to analyze the data were averages, standard deviation, and content analysis to collect information, group conversation, workshop, and expert-based seminars. The results of the research revealed that promoting conditions and equality: people with disabilities and their caregivers are knowledgeable about the rights of persons with disabilities and equality. The promotion problem was the lack of doctors to go to remote areas. There were 7 strategies for rights promotion. The results of the evaluation of rights promotion strategies found that all strategies were consistent, appropriateness, feasibility, and usefulness at a high level.